Food Web Trophic Structure at Marine Ranch Sites off the East Coast of Korea - Kang, Hee Yoon; Lee, Young-Jae; Kim, Changseong; Kim, Dongyoung; Kim, Doo-Ho; Kim, Jun-Ho; Choi, Dong-Lim; Kang, Chang-Keun (Frontiers in Marine Science, 2021)
Understanding the trophic ecology of the giant Pacific octopus Enteroctopus dofleini is challenging in developing marine ranches and in reestablishing its regional stocks against the severe stress of fishing. We adopted carbon and nitrogen stable isotope techniques (termed δ13C and δ15N, respectively) to identify the trophic niche (i.e., pathways and positions) of this species systematically in the entire food webs of two marine ranches off the east coast of the Korean peninsula. While a slight spatial shift in the isotopic nestedness of faunal communities was observed, the δ13C and δ15N values of consumers were distinct and separate among functional groups at both ranches. The consumer δ13C values spanned a broad range between pelagic and benthic sources of organic matter, and their δ15N values recorded a stepwise trophic-level enrichment, indicating that suspension feeders and herbivore-deposit feeders served as baselines of pelagic- and benthic-based trophic pathways, respectively. The δ13C values of predators, including E. dofleini, were arrayed between the two primary consumer groups. Neither δ13C nor δ15N values showed any remarkable variations with increasing octopus weight. Dietary mixing-model calculations indicated that E. dofleini is a generalist predator relying on both benthic- and pelagic-affinity prey, similar to some teleost species that consume a diverse spectrum of prey. In contrast, other teleost groups showed prevalent trophic links with either pelagic- or benthic-based pathways. The trophic-level estimations revealed that E. dofleini occupies an intermediate position slightly below the teleosts. A lack of discrete trophic positions between E. dofleini and teleosts seemed to be indicative of the released teleost predation but instead reflects the imposed food competition. Overall, the results demonstrated that despite compositional changes in the taxa constituting individual trophic groups, E. dofleini occupied a very similar trophic niche in both ranching systems. Finally, as extracted from information based on octopus marine ranches launched on natural rocky bottoms, our isotopic evidence provides a greater understanding of the trophic ecology of this octopus species in nearshore natural habitats along the southwestern margin of its distribution range.